Cardiac magnetic resonance findings and prognosis in type 1 myotonic dystrophy. Issue 6 (27th June 2023) - Leali, Marco; Aimo, Alberto; Ricci, Giulia; Torri, Francesca; Todiere, Giancarlo; Vergaro, Giuseppe; Grigoratos, Chrysanthos; Giannoni, Alberto; Aquaro, Giovanni Donato; Siciliano, Gabriele; Emdin, Michele; Passino, Claudio; et al.
Abstract : Background: Cardiac involvement is a major determinant of prognosis in type 1 myotonic dystrophy (DM1), but limited information is available about myocardial remodeling and tissue changes. The aim of the study was to investigate cardiac magnetic resonance (CMR) findings and their prognostic significance in DM1. Methods: We retrospectively identified all DM1 patients referred from a neurology unit to our CMR laboratory from 2009 to 2020. Results: Thirty-four patients were included (aged 45 ± 12, 62% male individuals) and compared with 68 age-matched and gender-matched healthy volunteers (43 male individuals, age 48 ± 15 years). At CMR, biventricular and biatrial volumes were significantly smaller (all P < 0.05), as was left ventricular mass ( P < 0.001); left ventricular ejection fraction (LVEF) and right ventricular ejection fraction (RVEF) were significantly lower (all P < 0.01). Five (15%) patients had a LVEF less than 50% and four (12%) a RVEF less than 50%. Nine patients (26%) showed mid-wall late gadolinium enhancement (LGE; 5 ± 2% of LVM), and 14 (41%) fatty infiltration. Native T1 in the interventricular septum (1041 ± 53 ms) was higher than for healthy controls (1017 ± 28 ms) and approached the upper reference limit (1089 ms); the extracellular volume was slightly increased (33 ± 2%, reference <30%). Over 3.7 years (2.0–5.0), 6 (18%) patients died of extracardiac causes, 5 (15%) underwent device implantation; 5 of 21 (24%) developed repetitive ventricular ectopic beats (VEBs) on Holter monitoring. LGE mass was associated with the occurrence of repetitive VEBs ( P = 0.002). Lower LV stroke volume ( P = 0.017), lower RVEF ( P = 0.016), a higher LVMi/LVEDVI ratio ( P = 0.016), fatty infiltration ( P = 0.04), and LGE extent ( P < 0.001) were associated with death. Conclusion: DM1 patients display structural and functional cardiac abnormalities, with variable degrees of cardiac muscle hypotrophy, fibrosis, and fatty infiltration. Such changes, as evaluated by CMR, seem to be associated with the development of ventricular arrhythmias and a worse outcome.